2016
DOI: 10.3727/096504016x14537290676865
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome in Definitive Concurrent Chemoradiation With Weekly Paclitaxel and Carboplatin for Locally Advanced Esophageal and Junctional Cancer

Abstract: There are little data on the efficacy and safety of taxane/platinum with definitive radiotherapy (RT) for esophageal/GEJ cancer. This article is a retrospective analysis of patients who received weekly paclitaxel 50 mg/m(2) and carboplatin AUC 2 with radical definitive RT for locally advanced esophageal/GEJ cancer. Between February 2011 and July 2014, 179 patients were included. The median age was 54 years. Ninety-two percent of patients had squamous histology. Mean RT dose was 58.7 Gy in 32 fractions over 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 16 publications
5
31
2
1
Order By: Relevance
“…Hyponatremia occurred at a relative high frequency (16-59%) in EC patients who previously received chemotherapy [17][18][19][20][21][22]. However, we found that the incidence of hyponatremia in treatment-naïve EC patients was only 2%.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Hyponatremia occurred at a relative high frequency (16-59%) in EC patients who previously received chemotherapy [17][18][19][20][21][22]. However, we found that the incidence of hyponatremia in treatment-naïve EC patients was only 2%.…”
Section: Discussioncontrasting
confidence: 55%
“…The incidence and prognostic value of hyponatremia in EC patients remains underestimated yet. In previous studies, hyponatremia occurred as an adverse event in 16% − 59% of EC patients who had received chemotherapy or chemoradiation [17][18][19][20][21][22]. However, hyponatremia induced by chemotherapy seemed not to be correlated with outcome of patients with EC [21].…”
mentioning
confidence: 93%
“…Combination of concurrent chemotherapy with taxane and platinum showed better tumor response in either adenocarcinoma or squamous cell carcinoma of the esophagus with acceptable toxicities [7,8,27,28]. If surgery is planned as a component of treatment, this regimen combined with reduction of neoadjuvant radiation does is feasible [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that patients who had a radiation dose of >50.4 Gy and chemotherapy <4 cycles had the worst survival. Possible reasons for this result Combination of concurrent chemotherapy with taxane and platinum showed better tumor response in either adenocarcinoma or squamous cell carcinoma of the esophagus with acceptable toxicities [7,8,27,28]. If surgery is planned as a component of treatment, this regimen combined with reduction of neoadjuvant radiation does is feasible [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…For a patient unable to undergo surgery, but able to tolerate chemotherapy plus radiotherapy, different regimens based on Oxaliplatin/Fluoropyrimidine [24] or carboplatin/paclitaxel [26] combinations may be an alternative to “classical” Cisplatin/5-fluorouracil schedule, due to their favorable toxicity profile (E:moderate; R: strong). If a patient is unable to tolerate combined therapy, chemotherapy alone is an option.…”
Section: Treatment For Non-metastatic Disease In Unfit Patientsmentioning
confidence: 99%